The influence of earthquake characteristics on the seismic performance of reinforced concrete buildings in Australia with varying heights. (15th May 2023) - Alothman, Aya; Mangalathu, Sujith; Al-Mosawe, Alaa; Alam, MD Morshed; Allawi, Abbas
Abstract: In Australia, most of the existing buildings were designed before the release of the Australian standard for earthquake actions in 2007. Therefore, many existing buildings in Australia lack adequate seismic design, and their seismic performance must be assessed. The recent earthquake that struck Mansfield, Victoria near Melbourne elevated the need to produce fragility curves for existing reinforced concrete (RC) buildings in Australia. Fragility curves are frequently utilized to assess buildings' seismic performance and it is defined as the demand probability surpassing capacity at a given intensity level. Numerous factors can influence the results of the fragility assessment of RC buildings. Among the most important factors that can affect the performance-based seismic assessment of buildings are the building height and the characteristics of the earthquake. Despite this, very few studies accounted for the earthquake characteristics and the influence of height on the vulnerability of buildings in Australia. Consequently, the combined effect of building height and the characteristics of the earthquake were investigated in this study. This was achieved through numerical modeling and time-history analyses of three typical two-, four-, and nine-story RC frame buildings in Australia. Moreover, these buildings were subjected to three different types of ground motions which were: short- and long-duration, and near-fault earthquakes. Fragility analysis was then conducted for the three buildings under all the selected earthquake suites. It was noted from the median values of the fragility curves that the four-story and the nine-story RC buildings were 17% and 18% more susceptible to damage in comparison with the two-story building under short-duration earthquakes. Moreover, it was also noted that the median value of the vulnerability increased by 33%, 40%, and 50% for the two-, four-, and nine-story buildings, sequentially, when subjected to near-fault compared to short-duration earthquakes. Highlights: Comparing the fragility analysis of buildings of different heights exposed to ground motions with different characteristics. Adopting three different earthquake suites to investigate the seismic performance assessment of the frame buildings. Assessing the seismic performance of three multi-story RC buildings using finite element software OpenSees. The IMK model was calibrated to experimental results to capture the hysteretic response of the RC elements in the FE model. Evaluating the fragility curves for three multi-story RC frame buildings under the selected ground motions.